Glambot SNAFH-R1: Lengan Kamera 4-DOF Biaya Rendah untuk Photobooth Indoor Berbasis Pengolahan Citra - oktavia, sanni; Hendry; Naufal, Muhammad; Satyawira, Ryan; Anuari, Nong; Cecillia, Febby; Suwandi, Agus; Erz Saragih, Raymond (Journal of Digital Ecosystem for Natural Sustainability, 2025)
Advances in automated cinematography have opened new possibilities in video production. This research focuses on the development of the Glambot 'SNAFH-R1,' a robotic camera system designed for controlled indoor environments, particularly for short video sessions and photo-booth applications. The system utilizes image processing techniques to track and capture dynamic shots, enhancing the experience for models and event participants. The robotic arm is equipped with a high-speed camera and programmed to execute smooth motion paths, creating cinematic effects. Experimental results demonstrate that the system can achieve precise and repeatable camera movements, improving video quality and user experience. This study highlights the feasibility of integrating image processing and robotics in creative video production, providing an automated and cost-effective solution for the entertainment industry.